CHEMICAL COMPOSITION, ANTIOXIDANT AND ANTIMICROBIAL PROPERTIES OF THREE ESSENTIAL OILS FROM PORTUGUESE FLORA - Martins, M. Rosário (2013)
The present work reports on the evaluation of chemical composition and antioxidant and antimicrobial activities of essential oils of three aromatic herbs, growing wild in the south of Portugal, used in traditional food preparations: Foeniculum vulgare, Mentha spicata and Rosmarinus officinalis. The principal components of essential oils were anethole (41.2%) for F. vulgare, carvone (41.1%) for M. spicata and myrcene (23.7%) for R. officinalis. Essential oils showed antioxidant activity either by DPPH radical scavenging method and system β- carotene/acid linoleic method. Antimicrobial activity of essential oils was observed against pathogenic bacteria and yeasts and food spoilage fungi. F.vulgare essential oil showed bacterial activity against Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa, Salmonella enteritidis, Staphylococcus aureus, Aspergillus niger and Fusarium oxysporum with MICs of 0.25-0.75mg/mL. M. spicata oil was active against E.coli, S.aureus, C.albicans, A. niger and F. oxysporum with MICs ranging between 0.25 and 0.75mg/mL. R. officinalis essential oil showed activity against E.coli and C.albicans with MICs of 0.5-1.0mg/mL. Having in account the important antioxidant and antimicrobial properties observed in present work, we consider that these essential oils might be useful on pharmaceutical and food industry as natural antibiotic and food preservative